The Influence of Health Education and Group Therapy on Adolescent Online Gamers’ Self-Concepts - Nurmagandi, Boby; Hamid, Achir Yani S.; Panjaitan, Ria Utami (European Journal of Mental Health, 2022)
Introduction: The rapid development of online games is currently marked by the increasing number of adolescent game players. This was particularly true during the COVID-19 pandemic that forced all activities to be done at home. Adolescents who play online games excessively, however, can risk their self-concept. Adolescents’ ability to control the increasing habit of playing online games can help them reduce the risk of self-concept problems by enhancing their adaptive behavior at their crucial psychosocial development stage. Health education and group therapy can be employed to attain this goal. Aims: The authors of this study aim to determine the effectiveness of health education and group therapy regarding the self-concept of adolescents who play online games excessively. Methods: As the research design, this study applied a quasi-experimental pre-posttest with a control group. The research respondents were selected using the stratified, proportional, and simple random sampling techniques. Seventy-six adolescents comprised the respondents of this study, divided into two groups. The respondents’ inclusion criteria were adolescents aged 15–16 years old who had played online games for at least the last 12 months. Results: The self-concept of adolescents in the intervention group has increased after implementing health education and group therapy (p < .05). In contrast to this, the self-concept of adolescents in the control group has not changed after implementing health education and group therapy (p > .05). Conclusions: Health education and group therapy effectively improve the self-concept of adolescent gamers.